Dementia in Latin America: Paving the way toward a regional action plan. Issue 2 (20th November 2020) - Parra, Mario Alfredo; Baez, Sandra; Sedeño, Lucas; Gonzalez Campo, Cecilia; Santamaría‐García, Hernando; Aprahamian, Ivan; Bertolucci, Paulo HF; Bustin, Julian; Camargos Bicalho, Maria Aparecida; Cano‐Gutierrez, Carlos; Caramelli, Paulo; Chaves, Marcia L. F.; et al.
Abstract: Across Latin American and Caribbean countries (LACs), the fight against dementia faces pressing challenges, such as heterogeneity, diversity, political instability, and socioeconomic disparities. These can be addressed more effectively in a collaborative setting that fosters open exchange of knowledge. In this work, the Latin American and Caribbean Consortium on Dementia (LAC‐CD) proposes an agenda for integration to deliver a Knowledge to Action Framework (KtAF). First, we summarize evidence‐based strategies (epidemiology, genetics, biomarkers, clinical trials, nonpharmacological interventions, networking, and translational research) and align them to current global strategies to translate regional knowledge into transformative actions. Then we characterize key sources of complexity (genetic isolates, admixture in populations, environmental factors, and barriers to effective interventions), map them to the above challenges, and provide the basic mosaics of knowledge toward a KtAF. Finally, we describe strategies supporting the knowledge creation stage that underpins the translational impact of KtAF.